2017
DOI: 10.3906/vet-1603-21
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of effects of fucoidan polysaccharides extracted from twospecies of Padina on the wound-healing process in the rat

Abstract: Seaweeds contains different types of polysaccharides with high abilities. The aim of this study was to determine the potential of fucoidan polysaccharides for wound-healing properties. Fucoidans of two species of Padina (P. tetrastromatica and P. boergesenii), collected from the Persian Gulf northern coastal area, were extracted and analyzed using high-performance anion-exchange chromatography. Purified fucoidans were used to prepare a 2% topical ointment. Under aseptic conditions, two identical paravertebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Kordjazi и соавт. одними из первых изучили ранозаживляющие свойства фукоиданов в эксперименте на ожоговых ранах, показали, что ПС из водорослей Padina tetrastomatic и Padina boergesenii индуцировали образование коллагена и регенерацию эпидермиса [13].…”
Section: Objectiveunclassified
“…Kordjazi и соавт. одними из первых изучили ранозаживляющие свойства фукоиданов в эксперименте на ожоговых ранах, показали, что ПС из водорослей Padina tetrastomatic и Padina boergesenii индуцировали образование коллагена и регенерацию эпидермиса [13].…”
Section: Objectiveunclassified
“…The wound healing effects of SPs from P. boergesenii (32.6% sulfate content) and P. tetrastromatica (19% sulfate content) indicate that superior healing activity was correlated with high sulfate content, which manifests as the degree of activation of fibroblast proliferation and function. [38] Moreover, a previous study examining the differential repairing effects of SPs from G. lemaneiformis at various molecular weights found that higher molecular weight limited the physical properties of SPs, such as their highly compact construction and massive molecular size, resulting in decreased possibility of migration to the cell membrane to exert their biological effects. [39] These results were confirmed in similar subsequent studies that SPs with low-molecular weight and increased sulfate levels accelerate dermal wound healing activity in excision rat model.…”
Section: Cytotoxicity and Wound Healing Activities Of Dsg And Its Der...mentioning
confidence: 99%
“…The results showed that fucoidan promoted dermal papillae re-surfacing and re-epithelialisation [142]. Wound dressings incorporating fucoidan exhibit a variety of abilities to optimise the healing process, including promoting collagen formation, promoting follicle regeneration, reducing inflammatory responses, reducing scar formation, and promoting angiogenesis [143][144][145][146]. Fucoidan and its derivatives are efficient in scavenging hydroxyl radicals and DPPH, exhibiting good antioxidant properties [147].…”
Section: Fucoidanmentioning
confidence: 99%